2007
DOI: 10.1530/eje-07-0250
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of adiponectin in children, adolescents and young adults with type 1 diabetes and the impact of age, gender, body mass index and metabolic control: a longitudinal study

Abstract: Objective: Adiponectin plays an important role in pathophysiology of obesity, type 2 diabetes and cardiovascular disease. The aim of this study was to determine adiponectin concentrations in children and adolescents with type 1 diabetes in a longitudinal manner and to study the impact of age, gender, body mass index (BMI) and metabolic control. Research design and methods: In this study, 88 children and adolescents with type 1 diabetes were followed longitudinally. At baseline and during follow-up, serum level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
33
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 48 publications
(78 reference statements)
11
33
2
1
Order By: Relevance
“…Similar results have been reported in the literature in type I DM [5][6][7][8][9], whereas type II DM has been associated with low serum adiponectin levels [10][11][12][13]. The increase in serum adiponectin levels in type I DM, in contrast to type II DM, may be due to a lack of insulin; glucose and insulin may play an important role in the increased serum adiponectin levels observed in type I DM [5,14] However, Berg et al showed that serum adiponectin levels do not change in mice after the onset of diabetes although the insulin levels decrease dramatically [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results have been reported in the literature in type I DM [5][6][7][8][9], whereas type II DM has been associated with low serum adiponectin levels [10][11][12][13]. The increase in serum adiponectin levels in type I DM, in contrast to type II DM, may be due to a lack of insulin; glucose and insulin may play an important role in the increased serum adiponectin levels observed in type I DM [5,14] However, Berg et al showed that serum adiponectin levels do not change in mice after the onset of diabetes although the insulin levels decrease dramatically [15].…”
Section: Discussionsupporting
confidence: 92%
“…We also did not find a correlation between adiponectin and TNF-α or IL-6 levels. Although many studies have described a role of TNF-α and IL-6 in insulin resistance, disturbed glucose tolerance and microangiopathy [9,[25][26][27][28][29], we were also unable to show such a relationship in our patients who had developed complications. Similar to our findings, studies have shown that serum leptin levels increase with BMI, female sex, puberty and diabetic nephropathy but do not differ between type I DM patients and healthy controls [16,[30][31][32][33].…”
Section: Discussioncontrasting
confidence: 76%
“…Earlier studies have shown higher adiponectin levels in adolescents with type 1 diabetes than in nondiabetic control participants, as well as a link between increased adiponectin levels and microalbuminuria [10]. Our study shows that these observations are modified by sex and age.…”
Section: Discussionsupporting
confidence: 67%
“…In adults with type 1 diabetes, higher adiponectin levels have been observed compared with controls [10], which, paradoxically, may be associated with microalbuminuria [11,12], reduced glomerular filtration rate [11,12], overt nephropathy and retinopathy [13]. Such observations conflict with data showing associations between insulin resistance and risk of microvascular complications in type 1 diabetes [14].…”
Section: Introductionmentioning
confidence: 95%
“…Although plasma leptin levels are elevated in obesity and type II diabetes mellitus (DM II), they are decreased in DM I and are positively associated with body mass index (BMI) (16,17). Adiponectin levels are increased in DM I (18,19) and decreased in DM II (20)(21)(22). Obesity is also characterized by hypoadiponectinemia, because adiponectin is inversely correlated with BMI (6,(8)(9)(10)19).…”
Section: Introductionmentioning
confidence: 99%